Redetermining the cutoff point of peristomal infection scoring: Methodological research. Issue 2 (3rd June 2021) - Ayhan, Hatice; Akcay, Kezban; Olmez, Yeter Nilgun; Simsek, Cem; Abbasoglu, Osman
Abstract: Background: Peristomal infections are a frequently encountered problem in enteral nutrition that warrants prompt diagnosis and early antimicrobial treatment. Current practice lacks a consensus on an accepted measurement tool with acknowledged validity and reliability. The Peristomal Infection Scoring System is one such tool that shows promise, yet the optimal cutoff value remains to be determined. Methods: This methodological research was conducted with 54 adult participants to evaluate their peristomal areas in terms of infection by two nurse nutritionists and an expert physician in a simultaneous and independent manner, using peristomal infection scoring or the local signs and symptoms of infection. Performance was assessed by the receiver operating characteristic curve, interobserver reliability, and validity metrics. Results: According to the expert physician's opinion, the peristomal infection rate was 9.2%. The agreement between the observers using the Peristomal Infection Scoring System was κ = 1, 000, P < .001. The peristomal infection scoring area under the receiver operating characteristic curve was 0.98 ( P < .001), and the best cutoff value was found to be 6 points, which correlated positively with a 0.88 coefficient ( P < .001) and an accuracy of 98.1% (CI, 90.11%–99.95%). Conclusion: The Peristomal Infection Scoring System with a cutoff value of 6 points is a valid and reliable instrument to diagnose peristomal infections. It can be easily used by healthcare professionals in all settings as needed.